2010
DOI: 10.1603/ec09372
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation Against <I>Aedes aegypti</I> Larvae of Aluminum-Carboxymethylcellulose-Encapsulated Spore-Toxin Complex Formulation of <I>Bacillus thuringiensis</I> Serovar <I>israelensis</I>

Abstract: The insecticidal activity after field exposure of an aluminum-carboxymethylcellulose microencapsulated formulation of Bacillus thuringiensis israelensis (Bti) spore-toxin complex, with malachite green as photoprotective agent, was evaluated using third-instar Aedes aegypti (L.) larvae in laboratory bioassays in Veracruz, México. Four insecticide treatments and an untreated control were compared at low and high doses over 96 d of field exposure under full sun or full shade conditions: 1) microencapsulated Bti s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Other factors that affect the toxicity of Bti are particle sedimentation (Rushed & Mulla, 1989), protein adsorption onto silt particles, organic matter, elevated temperatures (Ohana et al 1987), consumption by other organisms to which the toxin is not lethal (Blaustein and Margalit, 1991), dissolved tannins (Lord & Undeen, 1990) and inactivation by sunlight. Other factors that have been observed are that Bti does not recycle, under simulated field conditions, is unable to germinate and multiply in mud at the botton of pools although it did remain viable viable for up to 22 days, and higher water depth where applied decrease its activity (Ohana et al 1987) Early reports showed that a primary powder formulations of Bti had virtually no residual effect against mosquito larvae beyond application (Aguilar-Meza et al 2010), although the delta-endotoxin remained chemically stable in neutral and acid waters (Sinegre et al 1980). Extend persistence with Bti is possible through use of improved formulations.…”
Section: Field Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors that affect the toxicity of Bti are particle sedimentation (Rushed & Mulla, 1989), protein adsorption onto silt particles, organic matter, elevated temperatures (Ohana et al 1987), consumption by other organisms to which the toxin is not lethal (Blaustein and Margalit, 1991), dissolved tannins (Lord & Undeen, 1990) and inactivation by sunlight. Other factors that have been observed are that Bti does not recycle, under simulated field conditions, is unable to germinate and multiply in mud at the botton of pools although it did remain viable viable for up to 22 days, and higher water depth where applied decrease its activity (Ohana et al 1987) Early reports showed that a primary powder formulations of Bti had virtually no residual effect against mosquito larvae beyond application (Aguilar-Meza et al 2010), although the delta-endotoxin remained chemically stable in neutral and acid waters (Sinegre et al 1980). Extend persistence with Bti is possible through use of improved formulations.…”
Section: Field Applicationmentioning
confidence: 99%
“…Briquetts may result in more prolonged control than liquid formulations as these products have greater persistence through slow release (Kase & Branton 1986). On the other hand, Aguilar-Meza et al (2010) tested the residual insecticidal activity after field exposure of an aluminum-carboxymethylcellulose microencapsulated formulation of Bti spore-toxin complex with malachite green as photoprotective agent. The formulation improved the activity against Aedes aegypti larvae for 30 days and was comparable to that of the chemical insecticide temephos.…”
Section: Field Applicationmentioning
confidence: 99%
“…sun light and high temperature). 17,18 The consequent need of multiple applications makes biolarvicides an expensive solution and increases the possibility of the emergence of resistance in mosquitoes. 19 Therefore, to achieve an environmentally friendly formulation with a long shelf-life and efficacy, it is necessary to find an effective method to protect the active principle while simultaneously preventing its dispersion into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…israelensis produces parasporal crystals (Cry proteins) that are toxic to mosquito and black fly larvae (Diptera: Culicidae and Simuliidae) and that have been proven to be one of the most effective and potent microbial insecticides (Lacey 2007). Because the impact of mosquitoborne human diseases, such as dengue and dengue hemorrhagic fever, transmitted by Aedes aegypti (L.) (Diptera: Culicidae) is high, there is considerable interest in improving the efficacy of formulations of Bt israelensis against this vector (Ramírez-Suero et al 2005;Araújo et al 2007;Melo-Santos et al 2009;Aguilar-Meza et al 2010). Its effectiveness can be enhanced by expressing Bt israelensis cry genes in yeast and bacteria cells (Ogunjimi et al 2002;Quintana-Castro et al 2005) and by exploiting synergisms between different Bt israelensis toxins (Wu et al 1994;Poncet et al 1995) and between Bt israelensis toxins and other toxins (Frankenhuyzen et al 1991).…”
Section: Introductionmentioning
confidence: 99%